RESEARCH RESULTS OF DECOY DUCKECOLOGY - Lobanov Vladimir Aleksandrovich; Kaledin Anatoly Petrovich; Yuldashbayev Yusupzhan Artykovich; Filatov Anatoly Ivanovich; Ostapchuk Artem Mikhailovich; Makeeva Vera Mikhailovna; Stepanova Marina Vyacheslavovna; Baimukanov Dastanbek Asylbekovich (Scientific Journal of Pedagogy and Economics, 2020)
The results of long-term observations of the population of the Russian decoy duck in the nursery of decoy ducks of the Hunting Club with decoy and call ducks (HCDCD) and the study of its biology features are presented. As a result of these studies, significant differences were found between the exterior signs of mallard and decoy duck. The biology features of decoy ducks were studied, which led to changes in the process of domestication, molting, nutrition, reproduction, and behavioral changes characteristic of poultry (attitude to the aviary, people, and loss of migratory instinct). This showed that the Russian decoy duck is a breed of domesticated duck with specific hunting signs, which can be considered as a variety of domestic hunting duck with specific hunting features